Evaluation of a Rapid, Fully Automated Platform for Detection of BRAF and NRAS Mutations in Melanoma - Fanny Barel; Briac Guibourg; Laetitia Lambros; Glen Le Flahec; Pascale Marcorelles; Arnaud Uguen (Medical Journals Sweden, 2017)
BRAF and NRAS genetic analyses are time-consuming and can delay treatment choices in patients with metastatic melanomas presenting with acute deterioration. We compared the rapid, real-time, fully automated molecular diagnosis platform Idylla™ with next-generation sequencing (NGS) and immunohistochemistry for detection of BRAF and NRAS mutations in 36 patients with metastatic melanomas. The Idylla™ NRAS-BRAF-EGFRS492R mutation assay (110 min per sample) detected BRAF and NRAS mutations in 15 and 17 samples, respectively. One NRAS mutation was different between NGS and Idylla™ (NRASG13C vs. NRASG12A/D). Four samples were BRAF and NRAS wild-type. The global concordance between NGS and Idylla™ assays was 97.2% (35/36 cases). Immunohistochemistry was positive only in 9/9 BRAFV600E- and 6/6 NRASQ61R-mutated samples with VE1 and SP174 antibodies, respectively. The Idylla™ platform is a valuable rapid molecular diagnosis tool to reduce the delay in BRAF and NRAS analyses-related treatment choices for patients with metastatic melanoma presenting with acute deterioration.